The Effect of Transparency and Accountability of Village Fund Management on Community Welfare - Christin Natalia Mani; Nugraeni Nugraeni (Jurnal Syntax Admiration, 2024)
The objectives of this study are as follows: 1) To find out how transparent management of village funds affects the welfare of the people of Umanen Lawalu Village, Central Malaka District. 2) To find out how the Accountability of Village Fund Management affects the welfare of the Community of Umanen Lawalu Village, Central Malaka District. The research method used in this research is a quantitative method. Research methods are scientific procedures, practices, or procedures for obtaining data for research purposes that have certain useful and usable objectives. Based on the results and conclusions of the research, it shows that accountability and transparency in processing funds in Umanen Lawalu village, Central Malaka have a positive effect. If accountability and transparency are able to provide a positive response and are able to account for the proper use of funds for the community.